Ethnomathematics in the Bissu Traditional House of Pangkep Regency in Mathematics Learning Activities - Kusumayanti, Andi; Masnaeni, Masnaeni; Agustini, Jum'anil; Angriani, Andi Dian (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
This study aims to explore the application of ethnomathematics in the Bissu Traditional House in Pangkep Regency, South Sulawesi, by examining the various mathematical concepts embedded in the design and structure of the building. A qualitative method with an ethnographic approach was employed. Data were collected through direct observation, interviews with the guardians of the traditional house (Puang Matoa), and field documentation. The data were analyzed through the stages of reduction, presentation, and conclusion drawing. The findings reveal that the Bissu Traditional House incorporates concepts such as geometry, numerical patterns, proportionality, symmetry, and measurement. These concepts were then adapted into questions and contextual learning activities for the classroom, including calculating the volume of a triangular prism, analyzing symmetry, and determining stair gradients. This study demonstrates that ethnomathematics can serve as a bridge between mathematics learning and cultural preservation, fostering relevant, contextual, and meaningful learning experiences for students.